2022
DOI: 10.3389/fneur.2022.866673
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Conventional and Balloon-Guided Catheter-Assisted SWIM Technology for the Treatment of Acute Ischemic Stroke

Abstract: ObjectiveAcute ischemic stroke is common in elder patients. This study investigates whether using the balloon-guided catheter (BGC) would improve the effect of stent thrombectomy (Solitaire FR With Intracranial Support Catheter for Mechanical Thrombectomy, SWIM) for patients with acute ischemic stroke due to large vessel occlusion (AIS-LVO).MethodThe data of 209 patients with AIS-LVO underwent SWIM were collected retrospectively from January 2017 to June 2021. These patients were divided into two groups based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…The overall procedural complication rate was lower when using a non-BGC compared to a BGC with inflated balloon (aOR: 0.41, 95%CI 0.20-0.86). This result is in contrast to the literature, as previous studies have reported lower or comparable rates of complications when using a BGC with inflated balloon compared to a non-BGC [19,20]. This difference in complication rate may be partly explained by the way complications were registered in the current study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The overall procedural complication rate was lower when using a non-BGC compared to a BGC with inflated balloon (aOR: 0.41, 95%CI 0.20-0.86). This result is in contrast to the literature, as previous studies have reported lower or comparable rates of complications when using a BGC with inflated balloon compared to a non-BGC [19,20]. This difference in complication rate may be partly explained by the way complications were registered in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding the first-line thrombectomy technique, a meta-analysis showed improved clinical and procedural outcomes when using a BGC compared to a non-BGC when stent retriever only or direct aspiration only was used as first-line technique, but not when a combined technique was used as first-line technique [21]. This is in line with some literature showing no effect of using a BGC versus a non-BGC when the combined technique was used [12,20]. In subgroup analyses, we observed comparable results between the BGC groups when the combined technique was used as first-line technique.…”
Section: Discussionmentioning
confidence: 53%
“…Arguments against BGCs include their varying compatibility with certain MT devices, reported vascular complications 16 , and the opinion that the catheters used in MT procedures are enough to partially occlude antegrade flow and adequately reduce the risk of distal emboli [14][15] . In addition, a few studies have contradicted previous findings of BGC EVT superiority and demonstrated no significant difference in clinical or reperfusion outcomes between BGC and non-BGC EVT [18][19] , though these studies compared BGC SR-MT with combination SR-CAT. Notably, the most recent and largest study to demonstrate non-superiority of BGCs is the 2022 analysis of the ASSIST registry which assessed the outcomes of 1,300 thrombectomies and found no difference in FP or final RV scores between BGC EVT and non-BGC EVT groups 21 .…”
Section: Introductionmentioning
confidence: 87%